A Strength and Weakness of Regression Analysis and Quartile and IQR Deviation by using Test- Driven Development : Introduction; Background Theory; Proposed System; Discussion And Comparison Of Result; Conclusion - Myint Moe, Myint; Khine Oo, Khine (Discoveries in Agriculture and Food Sciences, 2020)
Test-Driven Development (TDD) derives an evolutionary approach which needs unit test cases to be made before implementation of the code. The goal of this paper is to examine product code quality and programmer productivity using test-driven development approach. This paper establishes regression analysis and quartile & inter-quartile range deviation to evaluate the process effect on external code quality and developer productivity. The results of this paper are that if developer productivity is the actual effect, external code quality will be fewer decreased and external code quality is the actual effect if developer productivity will be fewer reduced. Test-Driven Development can produce the clear of code, simple and bug-release. Defect numbers decreased when automated unit tests are written iteration related to test-driven development. If necessary, the code refactoring is acted TDD. This proposed system evaluates regression analysis and quartile & inter-quartile range deviation based on a fixed time-frame.